Detection of polymyxin-resistant Enterobacteriaceae from poultry farms in Brazil: continued mcr gene dissemination - Bruno Rocha Pribul; Kathelyn Soares dos Santos; Ramon Pimenta; Orlando Carlos da Conceição-Neto; Ana Paula D’Alincourt Carvalho-Assef; Miliane Moreira Soares de Souza; Cláudio Marcos Rocha-de-Souza (Brazilian Journal of Microbiology, 2026)
The emergence and persistence of plasmid-mediated polymyxin resistance in Brazilian poultry production pose a significant One Health challenge. Here, cloacal swabs from 202 broilers across four farms in the State of Rio de Janeiro yielded 125 Enterobacteriaceae isolates growing on polymyxin-EMB agar. Escherichia coli accounted for 99% of resistant isolates, with one Klebsiella pneumoniae . Multidrug resistance (MDR) was observed in 75% of polymyxin-resistant strains. PCR screening revealed mcr-1 and mcr-5 genes. Conjugation assays demonstrated horizontal transfer of mcr-1 plasmids (48.5–194 kb). MLST assigned key strains to ST10 and ST48, both within the high-risk CC10 lineage. These findings underscore the entrenched nature of polymyxin resistance despite regulatory bans, highlight the risk of zoonotic transmission of MDR determinants, and call for enhanced surveillance, biosecurity and alternative interventions to mitigate the spread of mobile polymyxin resistance in poultry environments.

Simultaneous inhibition of Listeria monocytogenes and modulation of quality attributes in Minas Frescal cheese by nanoencapsulated carvacrol - Thaís Benincá; Ana Carolina Silveira da Silva; Alina Scherer Pires; Dexter Pires Seider; Ana Carolina Ritter; Adriano Brandelli; Luana Schmidt; Jéssica Neto D'Avila; Paula Rossini Augusti; Patrícia da Silva Malheiros (Food Research International, 2026)

Potential drivers of Megninia ginglymura (Mégnin) distribution in poultry hens: rearing-system and oviposition microhabitat factors across humid and semi-arid regions - Iasmyn Vitória Cavalcanti Galvão; Maria Beatriz Gomes Duarte; Juan Sebastián D. Cáceres; Lídia Rafaele Almeida da Silva; Antônio Almeida Paz-Neto; Wilton Pires da Cruz; Noeli Juarez Ferla; José Wagner da Silva Melo (Veterinary Research Communications, 2026)
Megninia ginglymura (Mégnin, 1877) (Acariformes: Analgoidea: Analgidae) is a common feather mite of laying hens and a potential contributor to plumage damage and reduced productivity, yet its population dynamics and microhabitat use remain insufficiently characterized under modern commercial conditions. We conducted a year-long assessment of M. ginglymura abundance and intra-host distribution across three major production systems (Automated, Californian (two localities), and Cage-free), situated along a tropical–semi-arid gradient in a major poultry-producing region Pernambuco, Brazil. Monthly sampling of hens revealed pronounced temporal fluctuations in mite abundance, with peak infestations occurring during discrete periods of the production cycle and varying among systems. Cage-free flocks consistently exhibited the lowest infestation levels, whereas Automated and Californian systems showed higher abundances during the early months of monitoring. Female mites were evenly distributed across the five body regions examined, but eggs showed a strong and statistically supported concentration on wing feathers in all systems. This represents the first quantitative demonstration of spatially structured oviposition in M. ginglymura , revealing a clear mismatch between female distribution and egg deposition. These results have both ecological and applied implications: they suggest active microhabitat selection during oviposition and identify the wing region as a particularly sensitive diagnostic target for surveillance. By integrating temporal dynamics, housing effects, and spatial organization on the host, this study advances the understanding of M. ginglymura ecology and provides practical guidance for monitoring strategies in modern laying hen production.

P125 Sex-sorting conventional frozen semen—“reverse sorting”—results in viable pregnancies from ICSI-produced embryos - J.C. Samper; C. Gongora; L. Russel; C.R. Neto; R. Juras; D. Scofield (Journal of Equine Veterinary Science, 2026)

128 Assessment of pulsing and extrusion dynamics in vitrified equine ICSI embryos under different warming protocols - C.Z. Rodrigues; V.K. Lindsay; C.T.C. Okada; G.P. Correa; M. Azevedo; D. Rossety; C.R. Neto; G.D. Catandi (Journal of Equine Veterinary Science, 2026)

103 Germinal vesicle to metaphase II: Transcriptomic dynamics of single-equine oocytes following holding and in vitro maturation - S.B. Cousseau; V. Medina; C.R. Neto; M.S. Lindley; S. Loux; M.C. Azevedo; D. Rosseti; M. Mitchell; C.R.F. Pinto (Journal of Equine Veterinary Science, 2026)

Comparing species richness estimators for nested and sequential sampling designs: contrasting Bayesian hierarchical models against conventional estimators - Timothy R. Toavs; Pedro Peres-Neto; Julian D. Olden; Brandon K. Peoples; Stephen R. Midway (Community Ecology, 2026)
Assessing species richness (i.e., the number of species in a specific area) is of significant ecological relevance across theoretical, empirical, and practical applications. Accurately estimating species richness remains a persistent statistical challenge, as direct species counts are often unreliable. Consequently, numerous species richness estimation methods have been developed to accommodate a wide range of data types, research goals, assumptions, and sampling designs. The advent of extensive ecological databases and advanced computational capabilities has created new opportunities to apply sequential sampling designs, such as (hierarchically) nested approaches, for more accurate species richness estimation by recording the presence or absence of species over time and space (i.e., across multiple communities or sampling areas). We propose leveraging large-scale datasets by incorporating random effects into non-linear asymptotic functions. In this framework, species richness is treated as a random variable drawn from an estimable distribution. Specifically, we introduce Bayesian hierarchical models in this framework to estimate species richness. We compare our proposed Bayesian models to traditional estimators through simulations and an empirical example of stream fish communities, hierarchically nested within watersheds at the continental scale. The conventional Chao2 performed best, but our findings indicate that Bayesian hierarchical models provide species richness estimates that are comparable in bias and accuracy to traditional estimators, while offering greater precision. However, this gain in precision may come with trade-offs, such as sensitivity to model assumptions or potential biases in certain scenarios.

Chemical composition and biological activities of Momordica charantia leaves: a review - Tiago Feitosa Ribeiro; Isabela Araujo e Amariz; Emanuella Chiara Valença Pereira; Cícero André Ferreira Macedo; Nathália Andrezza Carvalho de Souza; Camila Gomes de Melo; Pedro José Rolim Neto; Raimundo Gonçalves de Oliveira Junior; Henrique D. M. Coutinho; Larissa Araújo Rolim (Phytochemistry Reviews, 2026)
Momordica charantia is a climbing plant popularly known as melon-de-São-Caetano, erva-de-São-Vicente, fruit-de-snake, melonzinho and gourd-de-São-Caetano. Its traditional use in folk medicine, associated with a wide range of therapeutic effects—such as antioxidant, anthelmintic, anti-inflammatory, antifungal, gastroprotective, hepatoprotective and antihyperglycemic activities—has aroused scientific interest and motivated the performance of pharmacological analyses to investigate and prove such properties. Thus, the objective of the present study was to carry out a systematic review (SR) composed of studies to analyze the chemical composition and biological activities of M. charantia leaves. The systematic review followed the PRISMA protocol, with searches in the Lilacs, PubMed and SciElo databases, using descriptors related to M. charantia leaves. Original non-clinical articles, published between 2000 and March 2020, that evaluated the chemical composition and biological effects of the plant were considered. Initially, 542 publications were identified, resulting in 479 after removal of duplicates. After screening and exclusion based on specific criteria, 131 articles were fully evaluated, with 42 included in the final analysis. Brazil, Japan, and China accounted for the largest number of publications. Despite this, 92% of the studies demonstrated adequate statistical treatment and information on doses and routes of administration, while 54% mentioned submission to the animal ethics committee. Hypotheses and objectives were clearly described in 69% of the studies. Randomization and blinding were indicated as essential to reduce bias in nonclinical studies. The systematic review confirmed the significant pharmacological potential of M. charantia leaves, driven by triterpenoids, flavonoids, saponins, and tannins. Their activities point to promising clinical applications in three areas: combating resistant infections (antimicrobial effect), controlling metabolic diseases (antihyperglycemic potential), and acting as a chemopreventive agent (antitumor and antioxidant actions). The low reported toxicity supports their pharmaceutical viability. However, the analysis highlighted a critical need for rigorous methodological standardization in non-clinical studies (adherence to ethics, blinding, randomization) to reduce bias and guarantee data reliability. Comprehensive phytochemical, pharmacological, and toxicological studies are thus indispensable. Targeted investment in research and standardization is vital to transform this proven medicinal potential into a globally validated and safe therapeutic product.

Testicular cryopreservation of prepubertal and adult Morada Nova rams: Slow freezing versus vitrification - R.H. Celiz; D.D. Guerreiro; D.C.C. Brito; M.A.S. Novaes; L.V.S. Ñaupas; N.A.R. Sá; G.J.Q. Palomino; F.D.R. Gomes; A.C.A. Ferreira; T.G. Mbemya; C.C.L. Fernandes; L.A.L. Rufino; et al. (Animal Reproduction Science, 2026)

Mantle compositional architecture and diamond potential of the Alto Paranaíba Igneous Province, Brazil: Insights from garnet xenocryst compositions in kimberlites - Julia C. Bandeira; Rogério G. Azzone; Luanna Chmyz; D. Graham Pearson; Izaac Cabral-Neto; Excelso Ruberti; Vincenza Guarino; Luísa D.V. Carvalho; Qiwei Zhang; Chiranjeeb Sarkar; Lina M. Cetina; Antônio Vítor Braga do Espírito Santo (Lithos, 2026)

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Graphene oxide enhances post-thaw sperm quality in tropically-adapted rams - Francisca N.M. Almeida; Denise D. Guerreiro; Alan M. Araújo; Bruno R.M. Costa; Eduardo R. Pessoa; Gaby J.Q. Palomino; Aderson M. Viana Neto; Luciano P. Silva; Valder N. Freire; Arlindo A. Moura (Animal Reproduction Science, 2026)

Repellent activity and toxicity of the essential oil of Calyptranthes concinna DC. using the model insect Drosophila melanogaster - M. S. Costa; T. S. Freitas; M. A. S. Oliveira; N. J. S. Araujo; S. P. Silva; Z. S. Silveira; N. S. Macêdo; J. C. Andrade-Pinheiro; H. S. Santos; A. M. R. Teixeira; F. A. B. Cunha; Ivo C. Pita Neto; et al. (Brazilian Journal of Botany, 2026)
Insects, belonging to the phylum Arthropoda, play essential roles in ecosystems, play essential roles in ecosystems, such as pollination, pest control, and decomposition. However, some species are vectors of diseases, which makes the development of control methods crucial. The use of synthetic insecticides, although effective, causes serious environmental and health problems. As an alternative, plant essential oils, which are biodegradable and can have repellent and toxic effects on insects, have gained prominence. This study focuses on the species Calyptranthes concinna DC., belonging to the Myrtaceae family, whose repellent and toxicological properties were evaluated using Drosophila melanogaster Meigan (1830) as an experimental model. The botanical material of Calyptranthes concinna was collected from the Private Natural Heritage Reserve in Palmeira-PR, and the essential oil was extracted from the dried leaves by hydrodistillation. The oil, with a yield of 0.26%, was stored for later analysis. The species Drosophila melanogaster was used as a model for toxicity and repellent activity tests. The tests involved fumigation of flies with different doses of oil, evaluation of damage to locomotor capacity and repellency test using filter paper. Data were analyzed statistically using two-way ANOVA. Calyptranthes concinna essential oil demonstrated low toxicity to Drosophila melanogaster , with 100% survival at all concentrations tested over 48 h and deaths that were not statistically significant compared to the water control. Impairment of locomotor capacity was observed only at the highest concentrations (40 µg/mL) after 3 h, and at intermediate concentrations (20 µg/mL) after 6 h, but these effects were equal to the control after 12 h. The repellency test revealed that the essential oil has a significant efficacy, especially at higher concentrations (39 µg/cm 2 ), comparable to the commercial repellent DEET, indicating that C. concinna essential oil is a promising alternative to synthetic repellents. Calyptranthes concinna essential oil has demonstrated potential as a natural repellent, with low toxicity and efficacy comparable to commercial DEET. Compared to studies with other essential oils and similar compounds, C. concinna oil has shown consistent results, suggesting that it may be an effective and environmentally friendly alternative to synthetic repellents. The presence of terpenes in the essential oil may be related to its repellent effect. These results support the use of C. concinna essential oil as a promising natural repellent.

Higher education settings menus have low compliance with the Mediterranean Diet and high carbon and water footprint: a case study from Portugal, Croatia and Turkey - B. Neto; D. Dikmen; L. Ferreira; C. Viegas; S. Filipec; L. Drobac; Z. Šatalić; A. Rocha (International Journal of Gastronomy and Food Science, 2026)

Parkia platycephala pod meal as a total replacement for Tifton-85 hay in high-concentrate diets for lambs: ingestive behavior, physiological, and metabolic parameters - Henrique N. Parente; Vanilsa C. Sousa; Gabrielle M. Oliveira; Osmar M. F. Neto; Gisele T. A. Silveira; Aylpy R. D. Santos; Juliana D. Oliveira; Anderson M. Zanine; Daniele J. Ferreira; Miguel A. Moreira Filho; Michelle O. M. Parente (Tropical Animal Health and Production, 2026)

Implementation of electrochemical treatment unit in an integrated offshore produced water treatment system - E. E. Schneider; M. A. P. Cechinel; S. E. Weschenfelder; D. G. Della Rocca; M. L. A. Albuquerque; S. L. de Carvalho Neto; L. P. Mazur; C. J. de Andrade; D. de Oliveira; R. F. P. M. Moreira (International Journal of Environmental Science and Technology, 2026)

First experimental determination of the 40Ar(n,2n)39Ar reaction cross section and 39Ar production in Earth’s atmosphere - S. Bhattacharya; M. Paul; R.N. Sahoo; R. Purtschert; H.F.R. Hoffmann; M. Pichotta; K. Zuber; D. Bemmerer; T. Döring; R. Schwengner; M.L. Avila; E. Lopez-Saavedra; et al. (Geochimica et Cosmochimica Acta, 2026)

Induction of oxidative stress and functional impairment by Doxorubicin in rat salivary glands - Guilherme Eduardo Rocha Silva; Ana Clara Emilio Padovezi; Renan José Barzotti; Larissa Victorino Sampaio; Rayara Nogueira de Freitas; Cristiane Furuse; Walid D. Fakhouri; Rafael Rodrigues Lima; Mariza Akemi Matsumoto; Antonio Hernandes Chaves-Neto (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Intestinal acinar adenocarcinoma in a blue-fronted Amazon parrot (Amazona aestiva) - João C. Krueger; Carolina Fontana; Arthur C. Cheng; Vinicius Dahm; Rachel Teixeira Neto; Luana Canavessi; Nelson D. Lucas; Luana C. Stunitz da Silva; Anderson Luiz de Carvalho; Aline de Marco Viott; Manoela M. Piva (Journal of Comparative Pathology, 2026)

Longitudinal effects of cerebrovascular reactivity and cerebral pulsatility in cognitively intact older adults with APOE4: links with cognition - Zacharie Potvin-Jutras; Pierre-Luc Tremblay; Hanieh Mohammadi; Sylvia Villeneuve; R. Nathan Spreng; Claudine J. Gauthier; Sylvia Villeneuve; Judes Poirier; John C.S. Breitner; Jennifer Tremblay-Mercier; Jordana Remz; Jean-Michel Raoult; et al. (GeroScience, 2025)

Leaf Nitrogen Spraying Improves Photosynthesis, Seed Quality and Yield of Soybean Plants Facing post-flowering Phosphorus Deficiency - Matheus D. Laira; Tamires S. Martins; Rafael L. Almeida; Venancio F. de Moraes-Neto; Juliana A. L. Pallone; Fernando C. B. Zambrosi; Rafael V. Ribeiro (Journal of Soil Science and Plant Nutrition, 2025)

Combined use of electrochemical, dissolved air flotation, and microfiltration in the treatment of offshore produced water - M. A. P. Cechinel; M. C. Proner; D. G. Della Rocca; S. L. de Carvalho Neto; S. E. Weschenfelder; A. da Silva; A. Ambrosi; M. Di Luccio; R. F. P. M. Moreira (International Journal of Environmental Science and Technology, 2025)

Selective IgM deficiency: evaluation of 75 patients according to different diagnostic criteria - Caroline Hamati Rosa Batista; Maria Carolina Martins Smanio; Pedro Borghesi Poltronieri; Leticia Leme Resende; Cristina Maria Kokron; Myrthes Toledo Barros; Rosana Camara Agondi; Natasha R. Ferraroni; Pérsio Roxo-Junior; Mariana Paes Leme Ferriani; Herberto Chong-Neto; Nelson Rosario Filho; et al. (Immunologic Research, 2025)

Genetic correlations between carcass traits measured by ultrasonography and semen quality traits in Nellore cattle incorporating genomic information - Camila S. Mussi; Gabriel C. Medeiros; Rafael Espigolan; Fernando Baldi; Marcio R. Silva; José D. Guimarães; Elisangela C. Matos; Joanir P. Eler; Tamires Miranda Neto; José Bento S. Ferraz; Luiz F. Brito (Livestock Science, 2025)

Trace element and U-Pb-Hf isotopic systematics of kimberlitic zircons: Classification, textures and implications for the origin of zircon “megacrysts” as antecrysts of variable antiquity - Soumendu Sarkar; Matthew F. Hardman; S. Andrew DuFrane; Izaac Cabral-Neto; Qiao Shu; D. Graham Pearson (Chemical Geology, 2025)

Paired megacrystic zircon (U-Th)/He and U/Pb dating reveals kimberlite eruption ages, protracted emplacement histories, and insights into megacryst genesis - Spencer D. Zeigler; Rebecca M. Flowers; D. Graham Pearson; Liam Courtney-Davies; Bruce A. Kjarsgaard; Stephen H. Richardson; Kaden Berkhahn; James R. Metcalf; Izaac Cabral-Neto (Chemical Geology, 2025)

Sex Drives Intraspecific Scaling of Home Range Size in Mammals - Aline Giroux; Denis Valle; Eliezer Gurarie; Marcus Vinicius Vieira; James D. Forester; Luca Börger; Raissa Sepulvida; Nicole Barbour; Erika G. da Rocha; Julia Oshima; Fernanda C. de Azevedo; Frederico G. Lemos; et al. (Ecology Letters, 2025)
Understanding variation in home range size (HR) provides important insights into the underlying ecological processes driving space use. However, it remains unclear whether the interspecific allometric scaling of mammals' HR can also be consistently observed within species and for both sexes. To address this knowledge gap, we GPS‐tracked 349 resident individuals across Brazil, encompassing 18 mammal species. We estimated individuals' HR and modelled intraspecific variation in HR against body mass (BM) and sex. While males showed a positive allometric scaling similar to interspecific findings reported in the literature (exponent = 1.23), females' BM had no statistically discernible relationship with HR. We suggest that males have greater energetic and evolutionary incentives to expand their HR with increasing BM, and more physical capacity to do so. Traditional studies on HR scaling that disregard individual sex may, in reality, reflect an average of two distinct patterns, while failing to accurately represent either one.

Paths to prosperity: How transport networks and income accessibility shape retail location - José B. Paiva Neto; Narciso F. Santos; Romulo D. Orrico Filho (Journal of Transport Geography, 2025)

Detrimental effects of anthropogenic disturbances on ant-mediated seed dispersal services: A global meta-analysis - Byanca N.T. Cavalcante; Diego Centeno-Alvarado; Fernanda M.P. Oliveira; José D. Ribeiro-Neto; Alexander V. Christianini; Xavier Arnan; Inara R. Leal (Perspectives in Plant Ecology, Evolution and Systematics, 2025)

Probing growth precursor diffusion lengths by inter-surface diffusion - Stoffel D. Janssens; Francisco S. Forte Neto; David Vázquez-Cortés; Fernando P. Duda; Eliot Fried (Computer Physics Communications, 2025)

Age and mantle source characteristics of kimberlite-derived zircons from Brazil revealed by U–Pb, Hf and O isotopes - Izaac Cabral-Neto; D. Graham Pearson; Excelso Ruberti; Yan Luo; Richard A. Stern; Rogério G. Azzone; Matthew F. Hardman; Vidyã V. Almeida; Francisco V. Silveira (Mineralogy and Petrology, 2025)

Improved trace element discrimination of kimberlitic and carbonatitic zircon: implications for zircon origin in kimberlite and the search for superdeep diamonds - Matthew F. Hardman; D. Graham Pearson; S. Andy DuFrane; Izaac Cabral-Neto; Rogério G. Azzone; Qiao Shu; Jason Hinde; Alexei S. Rukhlov (Mineralogy and Petrology, 2025)

β-Lactam Potentiating Activity, Molecular Docking, and ADMET Analysis of 3-Substituted Coumarins - José B. de Araújo-Neto; Daniel S. Alves; Gildênia A. de Araújo; Fernanda R. Ribeiro; Guilherme A. Brancaglion; Diogo T. Carvalho; Henrique D. M. Coutinho; Augusto Schrank; Saulo R. Tintino (Current Microbiology, 2025)

COVID-19 pandemic exacerbated food insecurity in South American countries - Carlos Frederico A. Vasconcelos-Neto; Michelle Jacob; Daniel Tregidgo; Denis Valle; Hani R. El Bizri; Sávio Marcelino Gomes; Julia E. Fa; Thais Q. Morcatty; Frederico Ozanan Barros Monteiro; Alessandra Scofield; Alessandra Matte; Willandia A. Chaves; et al. (Food Security, 2025)
The COVID-19 pandemic triggered unparalleled political, economic, and social ramifications, exacerbating global food insecurity (FI). To understand the overall impact of the pandemic and how different socio-economic groups were affected, we assessed prevalence and severity of FI in a sample of 18,997 households across seven countries in South America. We employed the Food Insecurity Experience Scale developed by the FAO. Our results showed that pre-pandemic, 4.5% of the sampled population across the entire continent faced Moderate FI, while 0.6% experienced severe FI. During the pandemic, Moderate FI increased to 16.9% (+ 12.4%), and Severe FI to 2.7% (+ 2.1%). By country, pre-pandemic households in Venezuela had the highest prevalence of Moderate FI (9.7%), with Peru experiencing the highest Severe FI frequency (1.1%). Peru had the greatest rise in Moderate (+ 23.9%) and Severe FI (+ 4.6%) during the pandemic. Low-income households, defined as those earning < 2 minimum wages per month, were most susceptible to FI. Uruguayan low-income families exhibited the most significant rise (+ 40.4%) in Moderate FI, while those in Peru experienced an increase of + 9.1% in Severe FI. This study measures the profound and far-reaching impact of the COVID-19 pandemic on FI in South America. Our findings also emphasise the critical importance of implementing effective public policy interventions to improve resilience against future shocks. This would enable policymakers to develop targeted strategies that address the immediate challenges posed by pandemics as well as laying the groundwork for a more resilient and sustainable food security landscape in the region.

Mortality rate and causes of death in inborn errors of immunity: A systematic review and meta-analysis - Saba Fekrvand; Zahra Hamidi Esfahani; Mohammadmehdi Yarahmadi; Ali Saeedi-Boroujeni; Helia Salehi; Ali Hakimelahi; Amir Almasi-Hashiani; Mahshid Rahmati; Sanaz Afshar-Ghasemlou; Najmeh Nameh Goshay Fard; Fateme Tarighat Monfared; Ehsan Khoshnezhad Afkham; et al. (Mutation Research - Reviews in Mutation Research, 2025)

Impact of sublethal treatments on dormant and non-dormant populations of Bacillus cereus spores during spray drying and on their recovery during whole milk powder storage - Verônica O. Alvarenga; Fernanda B. Campagnollo; Rosicléia A. Silva; Miriam D. Hubinger; Émilie Lang; Dionisio P. Amorim-Neto; Anderson S. Sant’Ana (International Dairy Journal, 2025)

Snow-Deposition Characteristics from X-Band Polarimetric SAR and Geospatial Analysis at Union Glacier, Antarctica - Christian Florian Göbel; Jorge Arigony-Neto; Ricardo Jaña; Rodrigo Gomez-Fell; Jean de Almeida Espinoza; Francisco Fernandoy; Ian D. Goodwin (Journal of the Indian Society of Remote Sensing, 2025)

Correction: Genomic prediction and QTL analysis for grain Zn content and yield in Aus-derived rice populations - Tapas Kumer Hore; C. H. Balachiranjeevi; Mary Ann Inabangan-Asilo; C. A. Deepak; Alvin D. Palanog; Jose E. Hernandez; Glenn B. Gregorio; Teresita U. Dalisay; Maria Genaleen Q. Diaz; Roberto Fritsche Neto; Md. Abdul Kader; Partha Sarathi Biswas; et al. (Journal of Plant Biochemistry and Biotechnology, 2025)

Influence of municipal solid waste composition on the shear strength of a landfill cell - V. E. A. G. Bahia; C. L. A. Neto; T. F. Silva; M. E. G. Boscov; V. E. D. Monteiro; M. C. Melo (International Journal of Environmental Science and Technology, 2025)

Development of Pickering emulsion from polycationic montmorillonite nanoclay - Iara C. Assunção Dorigon; Maria E. Araújo Pessoa; José C. Queiroz Neto; Debora V.F. Andrade Silva; José E. Soares Filho; Fabiola D. Silva Curbelo (Applied Clay Science, 2025)

Industry 4.0 technologies moderately spurred micro-level circular economy considering cleaner production, not promoting sustainable performance - G. C. de Oliveira Neto; D. da Silva; V. D. Arns; H. N. P. Tucci; L. F. R. Pinto; M. N. Seri (International Journal of Environmental Science and Technology, 2025)

GRANDlib: A simulation pipeline for the Giant Radio Array for Neutrino Detection (GRAND) - R. Alves Batista; A. Benoit-Lévy; T. Bister; M. Bohacova; M. Bustamante; W. Carvalho; Y. Chen; L. Cheng; S. Chiche; J.M. Colley; P. Correa; N. Cucu Laurenciu; et al. (Computer Physics Communications, 2025)

Genetic diversity, drug resistance, and biofilm formation in Klebsiella pneumoniae associated with nosocomial infection in Pelotas, RS, Brazil - Daniela R. Wozeak; Isabel L. Pereira; Thayná L. Cardoso; Amilton C. P. S. Neto; Daiane D. Hartwig (Brazilian Journal of Microbiology, 2025)

Novel tryptophyllin peptides from Physalaemus centralis inhibit oxidative stress-induced endothelial dysfunction in rat aorta preparation - Ariane Nogueira; José Brango-Vanegas; Andreanne G. Vasconcelos; Alex P. Coleone; Éder A. Barbosa; Daniel C. Moreira; Maria da Gloria da Silva; Wanessa F. Cabral; Jhones D. Nascimento; José Vinícius de Sousa França; Daniel Dias Rufino Arcanjo; Filipe Camargo D.A. Lima; et al. (Toxicon, 2025)

Characterization of the lipid profile of the equine sperm plasma membrane - D. Rodrigues; C. Ramires Neto; C. Freitas-Dell'Aqua; K.R. Belaz; D. Zampieri; A. Tata; M.N. Eberlin; F.F. de Souza; F.O. Papa; J.A. Dell'Aqua Júnior (Journal of Equine Veterinary Science, 2025)

Lipid profile differences in semen from “bad” and “good” freezer stallions - C. Ramires Neto; C.P. Freitas-Dell'Aqua; Y.F.R. Sancler-Silva; K.R. Belaz; D. Zampieri; A. Tata; M. Eberlin; F.O. Papa; J.A. Dell'Aqua; M.A. Alvarenga (Journal of Equine Veterinary Science, 2025)

Reactivity of amino acids and short peptide sequences: identifying bioactive compounds via DFT calculations - Daiane F. Oliveira; Alex P. Coleone; Filipe C. D. A. Lima; Augusto Batagin-Neto (Molecular Diversity, 2025)

Polymyxin resistance in Enterobacter cloacae complex in Brazil: phenotypic and molecular characterization - Bianca Santos da Costa; Renata Stavracakis Peixoto; Orlando Carlos da Conceição Neto; Leilane da Silva Pontes; Thamirys Rachel Tavares e Oliveira; Camila Bastos Tavares Teixeira; Ivson Cassiano de Oliveira Santos; Melise Chaves Silveira; Daiana Cristina Silva Rodrigues; Bruno Rocha Pribul; Cláudio Marcos Rocha-de-Souza; Ana Paula D.’Alincourt Carvalho-Assef (Brazilian Journal of Microbiology, 2024)

Impact of hydrophobic and hydrophilic surface properties on Pseudomonas aeruginosa adhesion in materials used in mineral water wells - Danilo Vilas Boas; Clara M. G. Lima; Larissa P. Margalho; Dionísio P. Amorim-Neto; Héctor D. S. Canales; Wilson J. F. Lemos Junior; Ana Carolina Ramos; Giancarlo Saraiva; Anderson S. Sant’Ana (Biofouling, 2024)

Construction and demolition waste as a low-cost adsorbent for water treatment: kinetics, isotherm, thermodynamics, and Fenton regeneration - Danilo H. S. Santos; Larissa F. Queiroz; Luiz D. Silva Neto; Keven E. Santos; Denio D. C. S. das Neves; Anamália F. Silva; Eduardo J. S. Fonseca; Daniel P. Fernandes; Lucas Meili (Environmental Science and Pollution Research, 2024)

Assessing interpreter’s disagreements in land cover reference data collection from historical Landsat time series in Amazon - Mariane S. Reis; Lucélia S. de Barros; Manoel R. Rodrigues Neto; Dayane Rafaela V. de Moraes; Noeli Aline P. Moreira; Gabriel Mikael R. Alves; Bruno V. Adorno; Cassiano Gustavo Messias; Luciano V. Dutra; Camilo D. Rennó; Sidnei João S. Sant’Anna; Maria Isabel S. Escada (International Journal of Remote Sensing, 2024)

Ataxia-telangiectasia in Latin America: clinical features, immunodeficiency, and mortality in a multicenter study - Renan A. Pereira; Ellen O. Dantas; Jessica Loekmanwidjaja; Juliana T. L. Mazzucchelli; Carolina S. Aranda; Maria E. G. Serrano; Elisabeth A. De La Cruz Córdoba; Liliana Bezrodnik; Ileana Moreira; Janaira F. S. Ferreira; Vera M. Dantas; Valéria S. F. Sales; et al. (Immunologic Research, 2024)

A new species of Diolcogaster (Hymenoptera: Braconidae) from Brazil of potential use in the biological control of the pest Hypercompe brasiliensis (Stoll) (Lepidoptera: Erebidae) - Geraldo Salgado-Neto; Alvaro D. dos Santos; Rozimar C. Pereira; Wagner de S. Tavares; José C. Zanuncio (Systematic Parasitology, 2024)

Photogrammetry scans for neuroanatomy education - a new multi-camera system: technical note - André S. B. Oliveira; Luciano C. P. C. Leonel; Megan M. J. Bauman; Alessandro De Bonis; Edward R. LaHood; Stephen Graepel; Michael J. Link; Carlos D. Pinheiro-Neto; Nirusha Lachman; Jonathan M. Morris; Maria Peris-Celda (Neuroinformatics, 2024)

Optimizing PtSn Composition in Direct Sugarcane Extract Fuel Cells: A Sustainable Bioenergy Solution - Bruno D. Q. Villardi; Victoria A. Maia; Julio Nandenha; Priscilla J. Zambiazi; Rodrigo F. B. de Souza; Almir O. Neto (Sugar Tech, 2024)

Genomic prediction and QTL analysis for grain Zn content and yield in Aus-derived rice populations - Tapas Kumer Hore; C. H. Balachiranjeevi; Mary Ann Inabangan-Asilo; C. A. Deepak; Alvin D. Palanog; Jose E. Hernandez; Glenn B. Gregorio; Teresita U. Dalisay; Maria Genaleen Q. Diaz; Roberto Fritsche Neto; Md. Abdul Kader; Partha Sarathi Biswas; et al. (Journal of Plant Biochemistry and Biotechnology, 2024)
Zinc (Zn) biofortification of rice can address Zn malnutrition in Asia. Identification and introgression of QTLs for grain Zn content and yield (YLD) can improve the efficiency of rice Zn biofortification. In four rice populations we detected 56 QTLs for seven traits by inclusive composite interval mapping (ICIM), and 16 QTLs for two traits (YLD and Zn) by association mapping. The phenotypic variance (PV) varied from 4.5% ( qPN 4.1 ) to 31.7% ( qPH 1.1 ). qDF 1.1 , qDF 7.2 , qDF 8.1 , qPH 1.1 , qPH 7.1 , qPL 1.2 , qPL 9.1, qZn 5.1 , qZn 5.2 , qZn 6.1 and qZn 7.1 were identified in both dry and wet seasons; qZn 5.1 , qZn 5.2 , qZn 5.3, qZn 6.2, qZn 7.1 and qYLD 1.2 were detected by both ICIM and association mapping. qZn 7.1 had the highest PV (17.8%) and additive effect (2.5 ppm). Epistasis and QTL co-locations were also observed for different traits. The multi-trait genomic prediction values were 0.24 and 0.16 for YLD and Zn respectively. qZn 6.2 was co-located with a gene ( OsHMA2 ) involved in Zn transport. These results are useful for Zn biofortificatiton of rice.

Ciliate diversity in rodrigo de freitas lagoon (Rio de Janeiro, Brazil) from an integrative standpoint - Pedro H. Campello-Nunes; Inácio D. da Silva-Neto; Thiago da S. Paiva; Carlos A. G. Soares; Noemi M. Fernandes (Brazilian Journal of Microbiology, 2024)

Effect of modified citrus pectin on galectin-3 inhibition in cisplatin-induced cardiac and renal toxicity - Diego D. Santos; Nycole M. Belote; Gisela R.S. Sasso; Rebeca D. Correia-Silva; Paulo C. Franco; Artur Francisco da Silva Neto; Fernanda T. Borges; Lila M. Oyama; Cristiane D. Gil (Toxicology, 2024)

Telocytes: current methods of research, challenges and future perspectives - Bruno D. A. Sanches; Francisco B. S. Teófilo; Mathieu Y. Brunet; Victor M. Villapun; Kenny Man; Lara C. Rocha; Jurandyr Pimentel Neto; Marta R. Matsumoto; Juliana S. Maldarine; Adriano P. Ciena; Sophie C. Cox; Hernandes F. Carvalho (Cell and Tissue Research, 2024)

GIS-FA: an approach to integrating thematic maps, factor-analytic, and envirotyping for cultivar targeting - Maurício S. Araújo; Saulo F. S. Chaves; Luiz A. S. Dias; Filipe M. Ferreira; Guilherme R. Pereira; André R. G. Bezerra; Rodrigo S. Alves; Alexandre B. Heinemann; Flávio Breseghello; Pedro C. S. Carneiro; Matheus D. Krause; Germano Costa-Neto; et al. (Theoretical and Applied Genetics, 2024)

Sperm traits and seminal plasma proteome of locally adapted hairy rams subjected to intermittent scrotal insulation - Aderson M. Viana Neto; Denise D. Guerreiro; Jorge A.M. Martins; F.ábio R. Vasconcelos; R.évila B.F. Melo; Ana Luiza M.C. S. Velho; Marta Neila-Montero; Rafael Montes-Garrido; Celso S. Nagano; Airton A. Araújo; Arlindo A. Moura (Animal Reproduction Science, 2024)

Resilience of Ricinus communis L. to high temperatures during germination and seedling growth resulting from efficient superoxide dismutase modulation - Valdir G. Neto; Wilco Ligterink; Henk W. M. Hilhorst; Isabela D. Santos; Carine R. Teixeira; Emily E. Santos; Marta B. Loureiro; Daniele Takahashi; Luzimar G. Fernandez; Paulo R. Ribeiro; Renato D. De Castro (Brazilian Journal of Botany, 2024)

Performance of spray nozzles and droplet size on glufosinate deposition and weed biological efficacy - Evandro P. Prado; Júlio C. Guerreiro; Pedro J. Ferreira-Filho; Vagner do Nascimento; Samuel Ferrari; Fernando S. Galindo; Marina Funichello; Carlos G. Raetano; Paulo H. Pagliari; Rodolfo G. Chechetto; Arthur D. Rodrigues Neto (Crop Protection, 2024)

Three snake venoms from Bothrops genus induced apoptosis and cell cycle arrest in K562 human leukemic cell line - Aline D. Marinho; Emerson Lucena da Silva; Adrhyann Jullyanne de Sousa Portilho; Laís Lacerda Brasil de Oliveira; Emanuel Cintra Austregésilo Bezerra; Beatriz Maria Dias Nogueira; Moema Leitão-Araújo; Maria Lúcia Machado-Alves; Carlos Correa Neto; Rui Seabra Ferreira; Caroline de Fátima Aquino Moreira-Nunes; Maria Elisabete Amaral de Moraes; et al. (Toxicon, 2024)

Droplet size and hydraulic spray nozzles in peanut plant spray deposition - Gabriela G. P. Buosi; Arthur D. R. Neto; Paulo R. M. Lopes; Samuel Ferrari; Júlio C. Guerreiro; Pedro J. F. Filho; Ronaldo C. Lima; Vagner Nascimento; Marina Funichello; Carlos G. Raetano; Evandro P. Prado (Journal of Plant Diseases and Protection, 2024)

Cardioprotective Effects of Leucine Supplementation against Doxorubicin-Induced Cardiotoxicity - Lucas C. Guimarães; Thiago M. Fidale; Talita C. R. Pereira; Paulo R. Lopes; Marcos D. Ferreira-Junior; Simone R. Deconte; Marcos L. Ferreira-Neto; Willams S. Brito; Rodrigo M. Gomes; Fernanda R. de Souza; Keilah V. N. Cavalcante; Gustavo C. Herrera; et al. (Cardiovascular Toxicology, 2024)

Melatonin acts through different mechanisms to control oxidative stress and primordial follicle activation and survival during in vitro culture of bovine ovarian tissue - Bianca R. Silva; Francisco C. Costa; Miguel F. De Lima Neto; Francisco F. Caetano Filho; Ernando I.T. de Assis; Francisco L.N. Aguiar; Anderson W.B. Silva; Solano D. Martins; Valdevane R. Araújo; Maria H.T. Matos; José J.N. Costa; José R.V. Silva (Domestic Animal Endocrinology, 2024)

Application of two- and multiway chemometric strategies for describing elementomic changes in pepper plants exposed to cadmium stress by multielement determination - Marcos de O. Ribeiro; Claudia B. de Abreu; Cindy S. Pinho; Lucas de O. Ribeiro; André D. de A. Neto; Leonardo S.G. Teixeira; Silvana M. Azcarate; Fabio de S. Dias (Chemosphere, 2023)

Toward sustainable harvest strategies for marine fisheries that include recreational fishing - Ashley M. Fowler; Natalie A. Dowling; Jeremy M. Lyle; Josep Alós; Leif E. Anderson; Steven J. Cooke; Andy J. Danylchuk; Keno Ferter; Heath Folpp; Clifford Hutt; Kieran Hyder; Daniel K. Lew; et al. (Fish and Fisheries, 2023)
Recreational fishing (RF) is a large yet undervalued component of fisheries globally. While progress has been made in monitoring, assessing, and managing the sector in isolation, integration of RF into the management of multi‐sector fisheries has been limited, particularly relative to the commercial sector. This marginalises recreational fishers and reduces the likelihood of achieving the sector's objectives and, more broadly, achieving fisheries sustainability. We examined the nature and extent of RF inclusion in harvest strategies (HSs) for marine fisheries across 15 regions in 11 nations to define the gap in inclusion that has developed between sectors. We focused on high‐income nations with a high level of RF governance and used a questionnaire to elicit expert knowledge on HSs due to the paucity of published documents. In total, 339 HSs were considered. We found that RF inclusion in HSs was more similar to the small‐scale sector (i.e., artisanal, cultural, or subsistence) than the commercial sector, with explicit operational objectives, data collection, performance indicators, reference points, and management controls lacking in many regions. Where specified, RF objectives focused on sustainability, economic value and catch allocation rather than directly relating to the recreational fishing experience. Conflicts with other sectors included competition with the commercial sector for limited resources, highlighting the importance of equitable resource allocation policies alongside HSs. We propose that RF be explicitly incorporated into HSs to ensure fisheries are ecologically, economically, and socially sustainable, and we recommend that fisheries organisations urgently review HSs for marine fisheries with a recreational component to close the harvest strategy gap among sectors.

Trace metals distribution along sediment profiles from the Doce River Continental Shelf (DRCS) 3 years after the biggest environmental disaster in Brazil, the collapse of the Fundão Dam - Valquíria M.C. Aguiar; Alex C. Bastos; Valeria da Silva Quaresma; Marcos Tadeu D’Azeredo Orlando; Fernanda Vedoato; Arthur S. Cavichini; José Antônio Baptista Neto (Regional Studies in Marine Science, 2023)

Strip Soil Tillage and Traffic Over the Soil on Sugar Cane Compared to Conventional Tillage Systems - Américo Ferraz Dias Neto; Daniel Albiero; Raffaella Rossetto; João D. Biagi; Jenyffer Gomes da Silva (Sugar Tech, 2023)

United we stand, divided we fall: in-depth proteomic evaluation of the synergistic effect of Mo -CBP 3 -PepI and Ciprofloxacin against Staphylococcus aureus biofilms - Nilton A. S. Neto; Tawanny K. B. Aguiar; Rayara J. P. Costa; Felipe P. Mesquita; Lais L. B. de Oliveira; Maria E. A. de Moraes; Raquel C. Montenegro; Rômulo F. Carneiro; Celso S. Nagano; Cleverson D. T. Freitas; Pedro F. N. Souza (Biofouling, 2023)

Preliminary assessment of toxicity of aerosol samples from central-west Brazil using Artemia spp. bioassays - Habdias A. Silva-Neto; Valtencir Zucolotto; Emmanuel B. D'Alessandro; Maria G.O. Tavares; Nelson R. Antoniosi Filho; Wendell K.T. Coltro; Guilherme M. Grosseli; Pedro S. Fadini; Roberta C. Urban (Chemosphere, 2023)

Assessment of the toxic effects of levetiracetam on biochemical, functional, and redox parameters of salivary glands in male Wistar rats - Gabriela Alice Fiais; Douglas Sadrac de Biagi Ferreira; Rayara Nogueira de Freitas; Lucas Guilherme Leite da Silva; Marcelo Kawaguchi; Allice Santos Cruz Veras; Giovana Rampazzo Teixeira; Cristina Antoniali; Rita Cássia Menegati Dornelles; Ana Cláudia de Melo Stevanato Nakamune; Walid D. Fakhouri; Antonio Hernandes Chaves-Neto (Toxicology, 2023)

Muscle proteome of crossbred cattle that received vitamin A at birth: impacts on meat quality traits - Rayssa S. Scapol; Welder A. Baldassini; Mohammed Gagaoua; Germán D. Ramírez-Zamudio; Márcio M. Ladeira; Mirele D. Poleti; José Bento S. Ferraz; Rodrigo de N.S. Torres; Juliana A. Torrecilhas; Guilherme L. Pereira; Otavio R. Machado-Neto; Rogério A. Curi; et al. (Livestock Science, 2023)

Biochar and Forage Peanut improve pastures: Evidence from a field experiment in Brazil - Agnieszka E. Latawiec; Aline F. Rodrigues; Katarzyna A. Korys; Maiara Mendes; Marcio Rangel; Ana Castro; Wenceslau Teixeira; Judson F. Valentim; Ednaldo Araujo; Luiz Fernando Duarte de Moraes; Vinicius Pacheco; Marcos Mendes; et al. (Agriculture, Ecosystems & Environment, 2023)

Metastatic Sertoli cell tumour in a captive giant anteater (Myrmecophaga tridactyla) - Clarissa H. Santana; Lucas dos R. de Souza; Laice A. da Silva; Ayisa R. Oliveira; Nayara F. de Paula; Daniel O. dos Santos; Fernanda M.A.M. Pereira; André D. Vieira; Letícia N. Ribeiro; Lauro L. Soares-Neto; Alexandre L. da Costa Bicudo; Alícia G. Hippolito; et al. (Journal of Comparative Pathology, 2023)

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

Mechanical behavior of cementitious composites reinforced with the fiber of sugarcane bagasse and glass wool waste - J. Preve Machado; T. C. da Silva; C. Henrique Borgert; L. Rosso Neto; D. Batista Gesuino; J. R. de Oliveira; T. Elias Allievi Frizon; F. Fardin Grillo; E. Junca (International Journal of Environmental Science and Technology, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Evaluation of phenotypic detection of carbapenemase-producing Pseudomonas spp. from clinical isolates - Ivson Cassiano de Oliveira Santos; Orlando Carlos da Conceiçāo Neto; Bianca Santos da Costa; Camila Bastos Tavares Teixeira; Leilane da Silva Pontes; Melise Chaves Silveira; Cláudio Marcos Rocha-de-Souza; Ana Paula D’Alincourt Carvalho-Assef (Brazilian Journal of Microbiology, 2023)

Freeze-dried Platelet-rich Plasma and Stem Cell-conditioned Medium for Therapeutic Use in Horses - Natália P.P. Freitas; Beatriz D'Almeida P. Silva; Marcus R.L. Bezerra; Laura Y.G. Pescini; Roberio G. Olinda; Cristiane Clemente de Mello Salgueiro; José F. Nunes; Jorge A.M. Martins; Saul G. Neto; Leonardo T. Martins (Journal of Equine Veterinary Science, 2023)

Karstified zone interpretation using deep learning algorithms: Convolutional neural networks applications and model interpretability with explainable AI - Marcos V.G. Jacinto; Adrião D. Doria Neto; David L. de Castro; Francisco H.R. Bezerra (Computers & Geosciences, 2023)

Addition of raw feedstocks and biochars to the soil on the sorption–desorption and biodegradation of 14C-saflufenacil - F. S. de Oliveira; V. Takeshita; K. F. Mendes; V. L. Tornisielo; F. G. Alonso; L. V. Junqueira; M. B. Neto; H. A. Lins; D. V. Silva (International Journal of Environmental Science and Technology, 2023)

Effects of dredging activities and seasonal variation on coastal plankton assemblages: results from 10 years of environmental monitoring - Lohengrin D. A. Fernandes; Guilherme N. Corte; Laura Moura; Carolina Reis; Thiago Matos; Danubia Moreno; Pedro Sant’ Anna Cortez; Wanderson Fernandes de Carvalho; Wanda Monteiro-Ribas; José Eduardo A. Gonçalves; Fernando Ribeiro; Fernanda Thomazelli; et al. (Environmental Monitoring and Assessment, 2023)

Predicting anoxia in the wet and dry periods of tropical semiarid reservoirs - Brenda Lara D.S. Carneiro; Maria de Jesus D Rocha; Mário U.G. Barros; Walt Disney Paulino; Iran E. Lima Neto (Journal of Environmental Management, 2023)

Molecular Detection of Rickettsia parkeri Strain Atlantic Rainforest in Ticks Parasitizing Small Mammals in Northeastern Brazil - Josiane M. Rocha; Philipe B. de Oliveira; Sócrates F. da Costa-Neto; Maria H. Ogrzewalska; Thiago F. Martins; João L. H. Faccini; Martin R. D. V. Alvarez; Hermes R. Luz; George R. Albuquerque (Acta Parasitologica, 2022)

Are the current commercially available oximes capable of reactivating acetylcholinesterase inhibited by the nerve agents of the A-series? - Marcelo C. Santos; Fernanda D. Botelho; Arlan S. Gonçalves; Daniel A. S. Kitagawa; Caio V. N. Borges; Taynara Carvalho-Silva; Leandro B. Bernardo; Cíntia N. Ferreira; Rafael B. Rodrigues; Denise C. Ferreira Neto; Eugenie Nepovimova; Kamil Kuča; et al. (Archives of Toxicology, 2022)

Modeling of Mechanized Sugarcane Harvesting to Support Decision-Making on Asset Management - Américo Ferraz Dias Neto; Daniel Albiero; Raffaella Rossetto; João D. Biagi (Sugar Tech, 2022)

Design and characterization of a pneumatic micro glass beads matrix sensor for soil water potential threshold control in irrigation management - Carlos Manoel Pedro Vaz; Luiz Fernando Porto; Carlos Ignácio D´Alkaine; Luis Henrique Bassoi; André Torre Neto; Jan W. Hopmans; Dennis E. Rolston (Irrigation Science, 2022)

Aridity, but not disturbance, reduces the specialization and modularity of plant–insect herbivore interaction networks in Caatinga dry forest - Pedro E. Santos-Neto; Xavier Arnan; José D. Ribeiro-Neto; Rainer Wirth; Inara R. Leal (Journal of Insect Conservation, 2022)

SIA‐BRA: A database of animal stable carbon and nitrogen isotope ratios of Brazil - Thaís Rovere Diniz‐Reis; Fernanda Gaudio Augusto; Adibe Luiz Abdalla Filho; Maria Gabriella da Silva Araújo; Siglea Sanna Freitas Chaves; Rodrigo Figueiredo Almeida; Elen Blanco Perez; Carla da Penha Simon; Janaína Leite de Souza; Cristiane Formigosa Gadelha da Costa; Taciana Figueiredo Gomes; Melissa Gaste Martinez; et al. (Global Ecology and Biogeography, 2022)
Motivation SIA‐BRA is a data set that compiles stable carbon (C) and nitrogen (N) isotope ratios of terrestrial and aquatic animals sampled in Brazilian biomes and coastal marine areas. Stable isotope ratios are helpful in animal ecology for several reasons; for instance, they can be used to investigate trophic niches, energy sources (diet tracing) and to track migration patterns. The Neotropics are considered one of the most undersampled regions of the world. Given that Brazil is a continental country where most of the dietary ecology of animal species is under‐assessed, we believe that the SIA‐BRA can provide important complementary information to address this gap in the literature. Additionally, the SIA‐BRA data set allows future investigations to address many questions concerning diet tracing, habitat use, food webs, foraging ecology, physiological aspects and effects of phylogeny on dietary ecology. Main type of variable investigated Carbon and nitrogen stable isotope ratios for terrestrial and aquatic animals. Spatial location and grain The SIA‐BRA included animal tissues sampled in 964 sites in the main Brazilian biomes and coastal marine areas. Time period The data represent information published and/or sampled from 1984 to 2021. Major taxa studied and measurement level The SIA‐BRA contains isotopic data of c . 21,804 non‐captive wildlife specimens, excluding livestock production or laboratory experiments. They were 13,881 vertebrates and 7,923 invertebrates. They were divided into the following habitats: terrestrial (30% of the total), freshwater (27%), oceanic (40%) and estuarine (4%). There were 11 phyla, with a clear dominance of Chordata (64%) and Arthropoda (29%), 36 classes, 154 orders, 473 families, 894 genera and 1,157 species. Software format Data are supplied as a comma‐delimited text file (.csv).

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Burkholderia perseverans sp. nov., a bacterium isolated from the Restinga ecosystem, is a producer of volatile and diffusible compounds that inhibit plant pathogens - Jackeline Pereira Andrade; Harisson Guimarães de Souza; Larissa Carvalho Ferreira; Margo Cnockaert; Evelien De Canck; Anneleen D. Wieme; Charlotte Peeters; Eduardo Gross; Jorge Teodoro De Souza; Phellippe Arthur Santos Marbach; Aristóteles Góes-Neto; Peter Vandamme (Brazilian Journal of Microbiology, 2021)

Treatment of gaseous effluent using a microalgae-based system - T. A. Pagioro; A. O. Rico; M. Soares; A. C. Sakuma; A. F. dos Anjos; P. R. da Costa Neto; M. Tiboni; J. D. Fontana (International Journal of Energy and Water Resources, 2021)

Predictive factors, outcomes, and molecular epidemiology of Clostridioides difficile diarrhea in Brazilian hospitals - Evelyne Santana Girão; Bruno de Melo Tavares; Sania Alves dos Santos; Gessica Lorena Gamarra; Camila Rizek; Roberta Cristina Martins; Lauro Vieira Perdigão Neto; Constancia Diogo; Tatiana D’ Annibale Orsi; Hugo Manuel Paz Morales; Keite da Silva Nogueira; Adriane Ceshin Maestri; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Disturbance‐induced emigration: an overlooked mechanism that reduces metapopulation extinction risk - Alexandre Mestre; Michael Barfield; James H. Peniston; Pedro R. Peres‐Neto; Francesc Mesquita‐Joanes; Robert D. Holt (Ecology, 2021)
Emigration propensity (i.e., the tendency to leave undisturbed patches) is a key life‐history trait of organisms in metapopulations with local extinctions and colonizations. Metapopulation models of dispersal evolution typically assume that patch disturbance kills all individuals within the patch, thus causing local extinction. However, individuals may instead be able to leave a patch when it is disturbed, either by fleeing before being killed or simply because the disturbance destroys the patch without causing mortality. This scenario may pertain to a wide range of organisms from horizontally transmitted symbionts, to aquatic insects inhabiting temporary ponds, to vertebrates living in fragmented forests. We generalized a Levins‐type metapopulation model of dispersal evolution by adding a new parameter of disturbance escape probability, which incorporates a second source of dispersal into the model: disturbance‐induced emigration. We show that disturbance escape expands the domain of metapopulation viability and selects for lower rates of emigration propensity when disturbance rates are high. The fitness gains from disturbance‐induced emigration are generally moderate, suggesting that disturbance escape might act more as a complementary dispersal strategy rather than a replacement to emigration propensity, at least for metapopulations that meet the assumptions of the Levins‐type model. Yet disturbance‐induced emigration may in some circumstances rescue a metapopulation from long‐term extinction when the combination of high disturbance rates and low local population growth rates compromises its viability. Further, a metapopulation could persist exclusively by disturbance escape if local carrying capacities are large enough to counterbalance two sources of mortality: mortality driven by disturbance and mortality during dispersal. This study opens two promising research lines: (1) the investigation of disturbance escape in metapopulations of ephemeral habitats with unsaturated populations and non‐equilibrium dynamics and (2) the incorporation of information costs to investigate the joint evolution of disturbance escape and emigration propensity.

Marine Streptomyces sp. Isolated From the Brazilian Endemic Tunicate Euherdmania sp. Produces Dihydroeponemycin and Analogs With Potent Antiglioma Activity - Luciana C. Furtado; Anelize Bauermeister; Rafael de Felicio; Raquel Ortega; Francisco das Chagas L. Pinto; João Agostinho Machado-Neto; Daniela B. B. Trivella; Otilia D. L. Pessoa; Diego V. Wilke; Norberto P. Lopes; Paula C. Jimenez; Leticia V. Costa-Lotufo (Frontiers in Marine Science, 2021)
Marine natural products have emerged as an important source for drug development, notably in the field of anticancer therapy. Still, the limited effectiveness of current therapies for central nervous system tumors indicates the need to identify new therapeutic targets and also novel pharmacological agents. In this context, proteasome inhibitors are appearing as a promising new treatment for these diseases. Herein, cytotoxic extracts produced by four marine bacteria recovered from the Brazilian endemic ascidian Euherdmania sp. were screened to evaluate their potential as proteasome inhibitors. The extract from marine Streptomyces sp. BRA-346 was selected for further investigation due to the potent proteasome inhibitory activity it displayed. Bioassay-guided fractionation led to an enriched fraction (proteasome inhibition IC 50 = 45 ng/mL), in which the presence of dihydroeponemycin (DHE), known for its proteasome inhibitory effect, and related compounds were annotated by mass spectrometry and further confirmed by comparison with DHE standard. Both DHE and the epoxyketone-containing fraction were evaluated in glioma cell lines, displaying high cytotoxicity in HOG and T98G cells (GI 50 of 1.6 and 1.7 ng/mL for DHE, and 17.6 and 28.2 ng/mL for the BRA-346 fraction, respectively). Additional studies showed that the epoxyketone-containing fraction (at GI 50 levels) led to an accumulation of ubiquitinated proteins and up-regulation of genes related to ER-stress response, suggesting treated cells are under proteasome inhibition. DHE induced similar effects in treated cells but at concentrations 25 times its GI 50 , suggesting that the other epoxyketone compounds in the bacteria extract derived fraction may contribute to enhance proteasome inhibition and further cellular effects in glioma cells. These findings revealed the molecular pathways modulated by this class of compounds in glioma cells and, moreover, reinforced the potential of this marine bacteria in producing a cocktail of structurally-related compounds that affect the viability of glioma cells.

Toxicity of methyl eugenol against Drosophila melanogaster and its myorelaxant activity in bronchioles isolated from Sus scrofa domesticus - Mikael A. de Souza; Luís Pereira-de-Morais; Zildene de S. Silveira; Nair S. Macêdo; Isaac M. Araujo; Luiz J. de L. Neto; Gyllyandeson de A. Delmondes; Roger H. S. da Costa; Lígia C. C. de Oliveira; Henrique D. M. Coutinho; Roseli Barbosa; Hélcio S. dos Santos; et al. (Biologia, 2021)

Potentiation of Antibiotic Activity by a Meldrum’s Acid Arylamino Methylene Derivative against Multidrug-Resistant Bacterial Strains - Maria M. C. da Silva; José B. de Araújo-Neto; Ana C. J. de Araújo; Priscilla R. Freitas; Cícera D. de M. Oliveira-Tintino; Iêda M. Begnini; Ricardo A. Rebelo; Luiz E. da Silva; Sandro L. Mireski; Michele C. Nasato; Maria I. L. Krautler; Jaime Ribeiro-Filho; et al. (Indian Journal of Microbiology, 2021)

Reduced cutaneous inflammation associated with antioxidant action after topical application of the aqueous extract of Annona muricata leaves - Luana M. Cercato; Jéssica M. D. Araújo; Alan S. Oliveira; Allan J. O. Melo; Bruno S. Lima; Edmilson W. P. dos Santos; Agenor G. dos S. Neto; Ricardo L. C. de Albuquerque-Júnior; Marcelo C. Duarte; Adriano A. S. Araujo; Ana Mara O. Silva; Renata Grespan; et al. (Inflammopharmacology, 2021)

Exploratory analysis in the evaluation of stress due to aluminum presence in Physalis angulata L. and multielement determination by microwave-induced plasma optical emission spectrometry (MIP OES) - Claudia B. de Abreu; Marcos de O. Ribeiro; Cyndi S. Pinho; Candice N. Carneiro; André D. de Azevedo Neto; Manuela O. de Souza; Fabio de S. Dias (Environmental Science and Pollution Research, 2021)

Correction to: α-Phellandrene attenuates tissular damage, oxidative stress, and TNF-α levels on acute model ifosfamide-induced hemorrhagic cystitis in mice - R. L. G. Gonçalves; F. V. M. Cunha; B. P. S. Sousa-Neto; L. S. A. Oliveira; M. E. Lopes; D. C. Rezende; I. J. O. Sousa; K. M. Nogueira; L. K. M. Souza; J. V. R. Medeiros; D. V. T. Wong; V. M. P. Pereira; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Insights on Zika virus envelope gene conservation in American outbreaks - Mateus V. Thomazella; Quirino A. Lima Neto; Francisco F. Duarte Junior; Fernando A. Jorge; Déborah de Castro Moreira; Amauri D. Leal Junior; Mayra M. Presibella; Irina N. Riediger; Rafael A. da Silva; Isabel Maria V. G. de Carvalho; Dennis A. Bertolini (Brazilian Journal of Microbiology, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

α-Phellandrene attenuates tissular damage, oxidative stress, and TNF-α levels on acute model ifosfamide-induced hemorrhagic cystitis in mice - R. L. G. Gonçalves; F. V. M. Cunha; B. P. S. Sousa-Neto; L. S. A. Oliveira; M. E. Lopes; D. C. Rezende; I. J. O. Sousa; K. M. Nogueira; L. K. M. Souza; J. V. R. Medeiros; D. V. T. Wong; V. M. P. Pereira; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Relationship between gain rate during the growing phase and forage allowance in the finishing phase in Nellore cattle - Verônica A. C. Mota; Rodolfo M. Fernandes; Laura F. Prados; João A. Alves Neto; Guilherme F. Berti; Flávio D. Resende; Gustavo R. Siqueira (Tropical Animal Health and Production, 2020)

Blockade of NOP receptor modulates anxiety-related behaviors in mice exposed to inescapable stress - Aldemara I. Silva; Victor A.D. Holanda; Joaquim G. Azevedo Neto; Edilson D. Silva Junior; Vanessa P. Soares-Rachetti; Girolamo Calo; Chiara Ruzza; Elaine C. Gavioli (Psychopharmacology, 2020)

Establishing Diorhabda carinulata: Impact of Release Disturbances on Pheromone Emission and Influence of Pheromone Lures on Establishment - Alexander M. Gaffke; Sharlene E. Sing; Tom L. Dudley; Daniel W. Bean; Justin A. Russak; Agenor Mafra-Neto; Robert K. D. Peterson; David K. Weaver (Journal of Chemical Ecology, 2020)

Natural Vs Managed Habitat: Effect Over the Seed-Predator Pachymerus nucleorum and Its Natural Enemies - J O S Silva; M L E Costa; B S Paixão; J D B Macêdo; P M S Rodrigues; E M F Lins-Neto (Neotropical Entomology, 2020)

Peeling the Otolith of Fish: Optimal Parameterization for Micro-CT Scanning - Jonas E. Vasconcelos-Filho; Felix S. L. Thomsen; Borko Stosic; Antonio C. D. Antonino; Daniel A. Duarte; Richard J. Heck; Rosangela P. T. Lessa; Francisco M. Santana; Beatrice P. Ferreira; Paulo J. Duarte-Neto (Frontiers in Marine Science, 2019)

Spatiotemporal responses of ant communities across a disturbance gradient: the role of behavioral traits - I. L. H. Silva; I. R. Leal; J. D. Ribeiro-Neto; X. Arnan (Insectes Sociaux, 2019)

The interaction of phylogeny and community structure: Linking the community composition and trait evolution of clades - William D. Pearse; Pierre Legendre; Pedro R. Peres‐Neto; T. Jonathan Davies (Global Ecology and Biogeography, 2019)
Aim Community phylogenetic studies use information about the evolutionary relationships of species to understand the ecological processes of community assembly. A central premise of the field is that the evolution of species maps onto ecological patterns, and phylogeny reveals something more than species traits alone about the ecological mechanisms structuring communities, such as environmental filtering, competition, and facilitation. We argue, therefore, that there is a need for better understanding and modelling of the interaction of phylogeny with species traits and community composition. Innovation We outline a new approach that identifies clades that are ecophylogenetically clustered or overdispersed and assesses whether those clades have different rates of trait evolution. Ecophylogenetic theory would predict that the traits of clustered or overdispersed clades might have evolved differently, in terms of either tempo (fast or slow) or mode (e.g., under constraint or neutrally). We suggest that modelling the evolution of independent trait data in these clades represents a strong test of whether there is an association between the ecological co‐occurrence patterns of a species and its evolutionary history. Main conclusions Using an empirical dataset of mammals from around the world, we identify two clades of rodents whose species tend not to co‐occur in the same local assemblages (are phylogenetically overdispersed) and find independent evidence of slower rates of body mass evolution in these clades. Our approach, which assumes nothing about the mode of species trait evolution but instead seeks to explain it using ecological information, presents a new way to examine ecophylogenetic structure.

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Multidisciplinary Scientific Cruise to the Rio Grande Rise - Luigi Jovane; James R. Hein; Isobel A. Yeo; Mariana Benites; Natascha M. Bergo; Paulo V. F. Corrêa; Daniel M. Couto; Ayrton D. Guimarães; Sarah A. Howarth; Henrique R. Miguel; Kira L. Mizell; Denise S. Moura; et al. (Frontiers in Marine Science, 2019)

A Review of High Impact Weather for Aviation Meteorology - Ismail Gultepe; R. Sharman; Paul D. Williams; Binbin Zhou; G. Ellrod; P. Minnis; S. Trier; S. Griffin; Seong. S. Yum; B. Gharabaghi; W. Feltz; M. Temimi; et al. (Pure and Applied Geophysics, 2019)

Recent advances on hydrometallurgical recovery of critical and precious elements from end of life electronic wastes - a review - Manivannan Sethurajan; Eric D. van Hullebusch; Danilo Fontana; Ata Akcil; Haci Deveci; Bojan Batinic; João P. Leal; Teresa A. Gasche; Mehmet Ali Kucuker; Kerstin Kuchta; Isabel F. F. Neto; Helena M. V. M. Soares; et al. (Critical Reviews in Environmental Science and Technology, 2019)

Recent advances in reproductive biology of stingless bees - A. Vollet-Neto; S. Koffler; C. F. dos Santos; C. Menezes; F. M. F. Nunes; K. Hartfelder; V. L. Imperatriz-Fonseca; D. A. Alves (Insectes Sociaux, 2018)

Modulation of antibiotic activity by the hydroalcoholic extract from leaves of Caryocar coriaceum WITTM - Luís J. de Lacerda Neto; A. G. B. Ramos; M. R. Kerntopf; H. D. M. Coutinho; L. J. Quintans-Junior; J. R. G. S. Almeida; J. Ribeiro-Filho; I. R. A. Menezes (Natural Product Research, 2018)

Ticks (Acari: Ixodidae) of the state of Amazonas, Brazil - Sergio L. Gianizella; Thiago F. Martins; Valeria C. Onofrio; Nair O. Aguiar; Waleska Gravena; Carlos A. R. do Nascimento; Laérzio C. Neto; Diogo L. Faria; Natália A. S. Lima; Monica R. Solorio; Louise Maranhão; Ivan J. Lima; et al. (Experimental and Applied Acarology, 2018)

Assessment of sexual maturity in captive Amazonian manatees ( Trichechus inunguis ) - Rodrigo S. Amaral; Vera M. F. Da Silva; Stella Maris lazzarini; José Anselmo D'affonsêca Neto; Daniella Ribeiro; Fernando C. W. Rosas (Marine Mammal Science, 2018)

Erratum to: Serum Markers of Neurodegeneration in Maple Syrup Urine Disease - Giselli Scaini; Tássia Tonon; Carolina F. Moura de Souza; Patricia F. Schuck; Gustavo C. Ferreira; Joao Seda Neto; Tatiana Amorim; Ida Vanessa D. Schwartz; Emilio L. Streck (Molecular Neurobiology, 2017)

Serum Markers of Neurodegeneration in Maple Syrup Urine Disease - Giselli Scaini; Tássia Tonon; Carolina F. Moura de Souza; Patricia F. Schuk; Gustavo C. Ferreira; Joao Seda Neto; Tatiana Amorin; Ida Vanessa D. Schwartz; Emilio L. Streck (Molecular Neurobiology, 2017)

Stability or breakdown under climate change? A key group of woody bamboos will find suitable areas in its richness center - Mônica A. Cupertino-Eisenlohr; Ronaldo Vinícius-Silva; Leonardo D. Meireles; Pedro V. Eisenlohr; João A. A. Meira-Neto; Ana Paula Santos-Gonçalves (Biodiversity and Conservation, 2017)

Combining phylogeny and co‐occurrence to improve single species distribution models - Ignacio Morales‐Castilla; T. Jonathan Davies; William D. Pearse; Pedro Peres‐Neto (Global Ecology and Biogeography, 2017)
Aim We present a novel quantitative framework that combines information on phylogeny and the spatial distributions of related species to enhance the single‐species distributional models commonly used in ecology. Innovation While species distribution models (SDMs) are becoming increasingly sophisticated, they rarely take into consideration the shared evolutionary histories of species. Species are not independent entities, and phylogenies may capture how species have configured their spatial distributions as a response to their ecological similarities and interactions in space and through evolutionary time. Our framework provides a flexible approach to include phylogenies as a surrogate for missing trait data within SDMs, and may be particularly valuable for disentangling current and historical drivers of species distributions and modelling data‐poor species when their close relatives are better sampled. Main conclusions Using both simulations and empirical examples, we demonstrate how the inclusion of phylogenetic information can significantly improve the fit of species distribution models by up to 30% for certain species. We show that the potential of phylogenies to improve model fit directly relates to the phylogenetic structure of species distributions and suggest that our framework has the potential to reconcile the apparent conflict between current and historical drivers of biodiversity patterns.

Effects of competition on fitness-related traits - A. D. Smith; A. L. S. Houde; B. Neff; P. R. Peres-Neto (Oecologia, 2017)

Influence of the current density on the electrochemical treatment of concentrated 1-butyl-3-methylimidazolium chloride solutions on diamond electrodes - Suzana M. L. de Oliveira Marcionilio; Gisele M. Alves; Rachel B. Góes e Silva; Pablo J. Lima Marques; Poliana D. Maia; Brenno A. D. Neto; José J. Linares (Environmental Science and Pollution Research, 2016)

The Influence of Fatty Acid Methyl Esters (FAMEs) in the Biochemistry and the Na+/K+-ATPase Activity of Culex quinquefasciatus Larvae - Lilian N. D. Silva; José A. Ribeiro-Neto; Jéssica M. M. Valadares; Mariana M. Costa; Luciana A. R. S. Lima; Luciano A. M. Grillo; Vanessa F. Cortes; Herica L. Santos; Stênio N. Alves; Leandro A. Barbosa (The Journal of Membrane Biology, 2016)

Brazilian recreational fisheries: current status, challenges and future direction - K. M. F. Freire; R. A. Tubino; C. Monteiro‐Neto; M. F. Andrade‐Tubino; C. G. Belruss; A. R. G. Tomás; S. L. S. Tutui; P. M. G. Castro; L. S. Maruyama; A. C. Catella; D. V. Crepaldi; C. R. A. Daniel; et al. (Fisheries Management and Ecology, 2016)
Recreational fisheries in Brazil have increased in importance and attracted many foreign recreational fishers. The objectives of this article were to summarise the available data on Brazilian recreational fisheries, to discuss some of their features and to analyse how they are performing in different regions compared with international trends. A review of published and unpublished sources together with data from recreational fishing licences was used. The participation rate was low (0.9%). Overall, there was a high diversity of fish species, with the following species/group of species repeatedly reported: Menticirrhus spp., Centropomus spp., Cynoscion spp., and Micropogonias furnieri (marine/estuarine water), and Cichla spp., Hoplias malabaricus , and Piaractus mesopotamicus , together with the introduced Oreochromis niloticus and Coptodon rendalli (fresh water). The north‐eastern region differs from the other regions: fishing occurs mostly in marine waters and fishers acquire mainly shore‐based licences, have minimum fishing expenditures and rarely release fishes. There is no estimate of the total harvest or economic value. Conflicts include catch‐and‐release‐oriented freshwater and marine recreational fishers vs consumption‐oriented coastal fishers, tournament participants vs non‐participants, commercial fishers and other leisure activities, pollution, ports, species introductions and translocations, protected areas, and federal and state laws. Cases of smooth shifts from artisanal to recreational fishing were detected, possibly associated with changes in the societal relationship with natural resources.

Detection of Subtle Hydromechanical Medium Changes Caused By a Small-Magnitude Earthquake Swarm in NE Brazil - V. D’Hour; M. Schimmel; A. F. Do Nascimento; J. M. Ferreira; H. C. Lima Neto (Pure and Applied Geophysics, 2016)

RNA-seq transcriptional profiling of Herbaspirillum seropedicae colonizing wheat (Triticum aestivum) roots - V. C. S. Pankievicz; D. Camilios-Neto; P. Bonato; E. Balsanelli; M. Z. Tadra-Sfeir; H. Faoro; L. S. Chubatsu; L. Donatti; G. Wajnberg; F. Passetti; R. A. Monteiro; F. O. Pedrosa; et al. (Plant Molecular Biology, 2016)

Rhizopus arrhizus and Fusarium solani Concomitant Infection in an Immunocompromised Host - João N. de Almeida Júnior; Karim Y. Ibrahim; Gilda M. B. Del Negro; Evandro D. Bezerra; Amaro N. Duarte Neto; Marjorie V. Batista; Rinaldo F. Siciliano; Mauro C. Giudice; Adriana L. Motta; Flávia Rossi; Ligia C. Pierrotti; Maristela P. Freire; et al. (Mycopathologia, 2016)

Effect of diets enriched with rutin on blood parameters, oxidative biomarkers and pituitary hormone expression in silver catfish (Rhamdia quelen) - Tanise S. Pês; Etiane M. H. Saccol; Giovana M. Ourique; Érika P. Londero; Luciane T. Gressler; Isabela A. Finamor; Daniel A. Rotili; Jaqueline I. Golombieski; Werner G. Glanzner; Susana F. Llesuy; Paulo B. D. Gonçalves; João Radünz Neto; et al. (Fish Physiology and Biochemistry, 2016)

ATXN3, ATXN7, CACNA1A, and RAI1 Genes and Mitochondrial Polymorphism A10398G Did Not Modify Age at Onset in Spinocerebellar Ataxia Type 2 Patients from South America - Fernanda S. Pereira; Thais L. Monte; Lucas D. Locks-Coelho; Amanda S. P. Silva; Orlando Barsottini; José L. Pedroso; Mario Cornejo-Olivas; Pilar Mazzetti; Clecio Godeiro; Fernando R. Vargas; Maria-Angélica F. D. Lima; Hélio van der Linden; et al. (The Cerebellum, 2015)

Ability of immunodiagnostic tests to differentiate between dogs naturally infected with Leishmania infantum and Leishmune®-vaccinated dogs - R. A. N. Ribeiro; R. G. Teixeira-Neto; V. S. Belo; E. C. Ferreira; H. D. F. H. Schallig; E. S. Silva (Veterinary Research Communications, 2015)

Trophic ecology and food consumption of fishes in a hypersaline tropical lagoon - P. H. Almeida‐Silva; R. A. Tubino; L. C. Zambrano; D. A. Hunder; S. R. Garritano; C. Monteiro‐Neto (Journal of Fish Biology, 2015)
This study evaluated the trophic ecology (diet composition, trophic strategy, similarities and overlap between species, feeding period and food consumption) of six benthivorous fish species in Araruama Lagoon, the largest hypersaline tropical lagoon on the east coast of South America, with an area of 210 km 2 and an average salinity of 52. The burrfish Chilomycterus spinosus fed on Anomalocardia flexuosa shell deposits, ingesting associated fauna. The caitipa mojarra Diapterus rhombeus differed from all other species, having not only the highest proportions of algae and Nematoda, but also feeding on polychaete tentacles. The two mojarras Eucinostomus spp. showed similar trophic strategies, feeding mostly on Polychaeta. The corocoro grunt Orthopristis ruber also fed mainly on Polychaeta, but differed from Eucinostomus spp. in secondary items. The whitemouth croacker Micropogonias furnieri fed mainly on small Crustacea at night, showing a high number of secondary prey items with low frequencies and high prey‐specific abundance. The daily food consumption (g food g −1 fish mass) for Eucinostomus argenteus was 0·012 and was 0·031 and 0·027 for M. furnieri in two different sampling events. The diet similarities between Araruama Lagoon and other brackish and marine environments indicate that hypersalinity is not a predominant factor shaping the trophic ecology of fishes in this lagoon. The stability of hypersaline conditions, without a pronounced gradient, may explain the presence of several euryhaline fishes and invertebrates well adapted to this condition, resulting in a complex food web.

Evaluation of the sensitivity to zinc of ciliates Euplotes vannus and Euplotes crassus and their naturally associated bacteria isolated from a polluted tropical bay - José Augusto Pires Bitencourt; Daniella C. Pereira; Inácio D. da Silva Neto; Mirian A. C. Crapez (Environmental Science and Pollution Research, 2015)

Soldier production in a stingless bee depends on rearing location and nurse behaviour - Francisca H. I. D. Segers; Cristiano Menezes; Ayrton Vollet-Neto; Dorothee Lambert; Christoph Grüter (Behavioral Ecology and Sociobiology, 2015)

3,4-Methylenedioxymethamphetamine (MDMA – Ecstasy) Decreases Neutrophil Activity Through the Glucocorticoid Pathway and Impairs Host Resistance to Listeria Monocytogenes Infection in Mice - V. Ferraz-de-Paula; A. Ribeiro; J. Souza-Queiroz; M. L. Pinheiro; J. F. Vecina; D. P. M. Souza; W. M. Quinteiro-Filho; R. L. M. Moreau; M. L. S. Queiroz; J. Palermo-Neto (Journal of Neuroimmune Pharmacology, 2014)

Photosynthesis, antioxidant activities and transcriptional responses in two sugarcane (Saccharum officinarum L.) cultivars under salt stress - Camila D. Medeiros; José R. C. Ferreira Neto; Marciel T. Oliveira; Rebeca Rivas; Valesca Pandolfi; Éderson A. Kido; José. I. Baldani; Mauro G. Santos (Acta Physiologiae Plantarum, 2014)

Ethanol Production from the Stem Juice of Different Sweet Sorghum Cultivars in the State of Pernambuco, Northeast of Brazil - Emmanuel D. Dutra; Adauto Gomes Barbosa Neto; Rafael Barros de Souza; Marcos Antonio de Morais Junior; Jose Nildo Tabosa; Rômulo Simões Cezar Menezes (Sugar Tech, 2013)

Plant functional types and traits as biodiversity indicators for tropical forests: two biogeographically separated case studies including birds, mammals and termites - Andrew N. Gillison; David E. Bignell; Kenneth R. W. Brewer; Erick C. M. Fernandes; David T. Jones; Douglas Sheil; Peter H. May; Allan D. Watt; Reginaldo Constantino; Eduardo G. Couto; Kurniatun Hairiah; Paul Jepson; et al. (Biodiversity and Conservation, 2013)

Determination of new immunoadjuvant saponin named QB-90, and analysis of its organ-specific distribution in Quillaja brasiliensis by HPLC - Juliane D. Fleck; Fernanda de Costa; Anna C.A. Yendo; Jéferson Segalin; Teresa C.T. Dalla Costa; Arthur G. Fett-Neto; Grace Gosmann (Natural Product Research, 2013)

Antifolates inhibit Cryptococcus biofilms and enhance susceptibility of planktonic cells to amphotericin B - R. Aguiar Cordeiro; C. I. Mourão; M. F. G. Rocha; F. J. Farias Marques; C. E. C. Teixeira; D. F. Oliveira Miranda; L. V. P. Neto; R. S. N. Brilhante; T. Jesus Pinheiro Gomes Bandeira; J. J. C. Sidrim (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Ion levels in the gastrointestinal tract content of freshwater and marine–estuarine teleosts - Alexssandro G. Becker; Jamile F. Gonçalves; Marcelo D. M. Burns; João Paes Vieira; João Radünz Neto; Bernardo Baldisserotto (Fish Physiology and Biochemistry, 2012)

Impact of coal tar pavement on polycyclic hydrocarbon distribution in lacustrine sediments from non-traditional sources - S. Froehner; D. B. de Souza; K. S. Machado; F. Falcão; C. S. Fernandes; T. Bleninger; D. M. Neto (International Journal of Environmental Science and Technology, 2012)

The seaweeds of Angola: the transition between tropical and temperate marine floras on the west coast of southern Africa - RJ Anderson; JJ Bolton; AJ Smit; D da Silva Neto (African Journal of Marine Science, 2012)

Water Deficit and Salt Stress Diagnosis Through LED Induced Chlorophyll Fluorescence Analysis in Jatropha curcas L. - E. A. Silva; A. S. Gouveia-Neto; R. A. Oliveira; D. S. Moura; P. C. Cunha; E. B. Costa; T. J. R. Câmara; L. G. Willadino (Journal of Fluorescence, 2012)

Diet and the risk of head and neck cancer: a pooled analysis in the INHANCE consortium - Shu-Chun Chuang; Mazda Jenab; Julia E. Heck; Cristina Bosetti; Renato Talamini; Keitaro Matsuo; Xavier Castellsague; Silvia Franceschi; Rolando Herrero; Deborah M. Winn; Carlo La Vecchia; Hal Morgenstern; et al. (Cancer Causes & Control, 2012)

Insects on urban plants: contrasting the flower head feeding assemblages on native and exotic hosts - Paula Perre; Rafael D. Loyola; Thomas M. Lewinsohn; Mário Almeida-Neto (Urban Ecosystems, 2011)

Accretion of Grenvillian terranes to the southwestern border of the Río de la Plata craton, western Argentina - Ricardo Varela; Miguel A. S. Basei; Pablo D. González; Ana M. Sato; Maximiliano Naipauer; Mario Campos Neto; Carlos A. Cingolani; Vinicius T. Meira (International Journal of Earth Sciences, 2011)

Immunoadjuvant saponin production in seedlings and micropropagated plants of Quillaja brasiliensis - Juliane D. Fleck; Joséli Schwambach; Manoela E. Almeida; Anna C. A. Yendo; Fernanda de Costa; Grace Gosmann; Arthur G. Fett-Neto (In Vitro Cellular & Developmental Biology - Plant, 2009)

The queen is dead—long live the workers: intraspecific parasitism by workers in the stingless bee Melipona scutellaris - D. A. ALVES; V. L. IMPERATRIZ‐FONSECA; T. M. FRANCOY; P. S. SANTOS‐FILHO; P. NOGUEIRA‐NETO; J. BILLEN; T. WENSELEERS (Molecular Ecology, 2009)
Insect societies are well known for their high degree of cooperation, but their colonies can potentially be exploited by reproductive workers who lay unfertilized, male eggs, rather than work for the good of the colony. Recently, it has also been discovered that workers in bumblebees and Asian honeybees can succeed in entering and parasitizing unrelated colonies to produce their own male offspring. The aim of this study was to investigate whether such intraspecific worker parasitism might also occur in stingless bees, another group of highly social bees. Based on a large‐scale genetic study of the species Melipona scutellaris , and the genotyping of nearly 600 males from 45 colonies, we show that ∼20% of all males are workers’ sons, but that around 80% of these had genotypes that were incompatible with them being the sons of workers of the resident queen. By tracking colonies over multiple generations, we show that these males were not produced by drifted workers, but rather by workers that were the offspring of a previous, superseded queen. This means that uniquely, workers reproductively parasitize the next‐generation workforce. Our results are surprising given that most colonies were sampled many months after the previous queen had died and that workers normally only have a life expectancy of ∼30 days. It also implies that reproductive workers greatly outlive all other workers. We explain our results in the context of kin selection theory, and the fact that it pays workers more from exploiting the colony if costs are carried by less related individuals.

Obesity and genetics regulate microRNAs in islets, liver, and adipose of diabetic mice - Enpeng Zhao; Mark P. Keller; Mary E. Rabaglia; Angie T. Oler; Donnie S. Stapleton; Kathryn L. Schueler; Elias Chaibub Neto; Jee Young Moon; Ping Wang; I-Ming Wang; Pek Yee Lum; Irena Ivanovska; et al. (Mammalian Genome, 2009)

Changes in tree and liana communities along a successional gradient in a tropical dry forest in south-eastern Brazil - Bruno G. Madeira; Mário M. Espírito-Santo; Santos D’Ângelo Neto; Yule R. F. Nunes; G. Arturo Sánchez Azofeifa; G. Wilson Fernandes; Mauricio Quesada (Plant Ecology, 2009)

Grazing protozoa and magnetosome dissolution in magnetotactic bacteria - Juliana L. Martins; Thaís S. Silveira; Fernanda Abreu; Karen T. Silva; Inácio D. Da Silva‐Neto; Ulysses Lins (Environmental Microbiology, 2007)
Summary Magnetotactic bacteria show an ability to navigate along magnetic field lines because of magnetic particles called magnetosomes. All magnetotactic bacteria are unicellular except for the multicellular prokaryote (recently named ‘ Candidatus Magnetoglobus multicellularis’), which is formed by an orderly assemblage of 17–40 prokaryotic cells that swim as a unit. A ciliate was used in grazing experiments with the M. multicellularis to study the fate of the magnetosomes after ingestion by the protozoa. Ciliates ingested M. multicellularis , which were located in acid vacuoles as demonstrated by confocal laser scanning microscopy. Transmission electron microscopy and X‐ray microanalysis of thin‐sectioned ciliates showed the presence of M. multicellularis and magnetosomes inside vacuoles in different degrees of degradation. The magnetosomes are dissolved within the acidic vacuoles of the ciliate. Depending on the rate of M. multicellularis consumption by the ciliates the iron from the magnetosomes may be recycled to the environment in a more soluble form.

Analysis of the composition of bacterial communities in oil reservoirs from a southern offshore Brazilian basin - Lara D. Sette; Karen C. M. Simioni; Suzan P. Vasconcellos; Lucia J. Dussan; Eugênio V. S. Neto; Valéria M. Oliveira (Antonie van Leeuwenhoek, 2007)

Acute cattle intoxication from Nerium oleander pods - B. Soto-Blanco; J. D. Fontenele-Neto; D. M. Silva; P. F. C. C. Reis; J. E. Nóbrega (Tropical Animal Health and Production, 2006)

Genomic variability of prune dwarf virus as affected by agricultural practice - F. Fonseca; J. D. Neto; V. Martins; G. Nolasco (Archives of Virology, 2005)

Control of development and valepotriate production by auxins in micropropagated Valeriana glechomifolia - C. M. Bello de Carvalho; N. Maurmann; D. I. Luz; A. G. Fett-Neto; S. B. Rech (Plant Cell Reports, 2004)

Observing bacterial activity interferometrically - D. Faragó Jardim; R. Batista Santiago Neto; R. R. P. Machado; F. M. Aarestrup; J. P. R. F. de Mendonça; B. Lesche (European Biophysics Journal, 2003)

Prevalence of GB Virus C (Hepatitis G Virus) and Risk Factors for Infection in São Paulo, Brazil - Ribeiro-dos-Santos G.; Nishiya A.; Nascimento C.; Bassit L.; Chamone D.; Focaccia R.; Eluf-Neto J.; Sabino E. (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

Safety Measures in the Application of Organophosphate Insecticides on Staked Tomato Crops Using Dragged Hoses - M. E. C. Queiroz; J. G. Machado-Neto; L. R. L. Pereira; F. Calixto; F. D. Amarolli; N. S. Arakawa; D. Carvalho (Bulletin of Environmental Contamination and Toxicology, 2002)

Spatial isolation and fish communities in drainage lakes - Julian D. Olden; Donald A. Jackson; Pedro R. Peres-Neto (Oecologia, 2001)

Soil temperature in a sugar-cane crop as a function of the management system - J.C.M. Oliveira; L.C. Timm; T.T. Tominaga; F.A.M. Cássaro; K. Reichardt; O.O.S. Bacchi; D. Dourado-Neto; G.M. de S. Câmara (Plant and Soil, 2001)

Risk of Intoxication with Sulfluramid in a Packing Plant of Mirex-S - J. G. Machado-Neto; M. E. C. Queiroz; D. Carvalho; A. J. Bassini (Bulletin of Environmental Contamination and Toxicology, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Behavioral ecology ofMyiopharus doryphorae (riley) andM. aberrans (townsend), tachinid parasitoids of the colorado potato beetle - E. R. López; L. C. Roth; D. N. Ferro; D. Hosmer; A. Mafra-Neto (Journal of Insect Behavior, 1997)